Effect of platelet template seeds on microstructure and thermoelectric properties of Ca3Co4O9 ceramics. Issue 2 (1st February 2019) - Shi, Zongmo; Xu, Jie; Zhu, Jihong; Zhang, Yi; Gao, Tong; Qin, Mengjie; Sun, Han; Dong, Gaogao; Gao, Feng
Abstract: Plate-like Ca3 Co4 O9 microcrystal particles were synthesized by molten salt synthesis. Denser Ca3 Co4 O9 thermoelectric ceramics were fabricated by utilizing morphologically optimized particles as the template seeds. Effects of Ca3 Co4 O9 template seeds on microstructure and thermoelectric properties of ceramics were investigated. The results showed that weight ratios of salt to oxides (s/o) had great influence on components, microstructure, and grain size of template seeds. The particles displayed satisfactory morphology and uniform grain size when the ratio of s/o reached 1, with a mean grain size of 7.92 µm in diameter and 1.13 µm in thickness. The bulk density of Ca3 Co4 O9 ceramics was 92.5% in the presence of 40 wt% of the template seed. The thermoelectric properties were measured from 50 °C to 800 °C. The results showed an electrical resistivity of 20.3 mΩ cm, a Seebeck coefficient of 179 μV/K and a power factor of 0.16 mW/m K 2 . The ZT value can reach 0.15 at 800 °C, which is 1.6 times higher than that of conventional Ca3 Co4 O9 thermoelectric ceramics.